2016
DOI: 10.1159/000447410
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Ventriculoperitoneal Shunt Failure in Children Undergoing Initial Placement or Revision

Abstract: Background: Ventriculoperitoneal (VP) shunt placement, the mainstay of treatment for hydrocephalus, can place a substantial burden on patients and health care systems because of high complication and revision rates. We aimed to identify factors associated with 30-day VP shunt failure in children undergoing either initial placement or revision. Methods: VP shunt placements performed on patients in the 2012-2013 American College of Surgeons National Surgical Quality Improvement Program (NSQIP) Pediatric were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…More recent studies continue to demonstrate imperfect shunt outcomes, with a 23% chance of shunt failure in the first 11 months in studies of children undergoing shunting, and a lifetime risk of shunt failure of 14.5% in adults undergoing shunting for various etiologies [10,11] . The etiology of hydrocephalus has also been shown to contribute to the shunt failure rate; both a history of intracranial masses, brain tumors, or congenital hydrocephalus, and a history of intraventricular hemorrhage (IVH) predispose patients to higher failure rates [10,12,13] . Shunt infections remain a relatively common and costly complication of shunting and will be discussed in more detail later.…”
Section: Initial Considerations In Hydrocephalus Treatmentmentioning
confidence: 99%
“…More recent studies continue to demonstrate imperfect shunt outcomes, with a 23% chance of shunt failure in the first 11 months in studies of children undergoing shunting, and a lifetime risk of shunt failure of 14.5% in adults undergoing shunting for various etiologies [10,11] . The etiology of hydrocephalus has also been shown to contribute to the shunt failure rate; both a history of intracranial masses, brain tumors, or congenital hydrocephalus, and a history of intraventricular hemorrhage (IVH) predispose patients to higher failure rates [10,12,13] . Shunt infections remain a relatively common and costly complication of shunting and will be discussed in more detail later.…”
Section: Initial Considerations In Hydrocephalus Treatmentmentioning
confidence: 99%
“…Infant hydrocephalus is often associated with developmental delay and multiple comorbidities [1,2]. Both surgical and neurodevelopmental outcomes (NDO) have been shown to vary depending on the aetiology of hydrocephalus, with mixed findings in the literature in terms of ventriculoperitoneal (VP) shunt failure rates [3][4][5][6][7]. The importance of measuring NDO, rather than surgical outcomes only, in paediatric hydrocephalus, has been emphasised [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…reported the prevalence of congenital hydrocephalus of 4.65/10,000 births in Europe. [ 5 ] Isaacs et al . in their study found that the prevalence of pediatric hydrocephalus between continents was almost higher in Africa 104.0/100,000 compared with North America 55.6/100,000.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have conveyed the pediatric shunt revision rate in the 1 st year after the placement with varying result. [ 2 , 5 , 9 , 10 ] However, the incidence of shunt failure following shunt revision in Indonesia remains unreported. Therefore, we presented a single-institution retrospective analysis regarding the CSF shunt revision ratio in the 1 st year placement.…”
Section: Introductionmentioning
confidence: 99%